Prithvi Narayan Shah’s Music Policy - K.C., Shree (SIRJANĀ – A Journal Of Arts and Art Education, 2018)
Most writers describe Prithvi Narayan Shah as someone who didn’t really appreciate music. However, his grooming in the palace with different rituals accompanied by musical chants of mantras and his attachment with his fellow friends in his childhood shows that he had adopted musical in a very cultural manner. In his ‘Divya Upadesh’, he has shown views of preserving and protecting Nepali culture by promoting Nepali music and Nepali artists. Bise Nagarchi, a musician helped Prithvi Narayan Shah in his unifying campaign by encouraging and refreshing the people at war through his music. This article will enlist points that showcase facts that show he was not against music and also review some of his ‘Dibya Upadesh’ through a more musical perspective. Both primary and secondary data have been used as the source of content in the making of this article.